Answers

2015-01-17T18:56:04+05:30
If x≤-1   then,
                       x²+x+1=x(x+1)+1≥1            since x and x+1  are both negative                           if -1 smaller than x smaller than 0  , then                                                               x²+x+1=x²+(x+1) greater than 0+0=0                                                             thus in other words convert it in form                                                                                                (d x+e)²+f=0
0